2013
DOI: 10.19030/jabr.v29i4.7976
|View full text |Cite
|
Sign up to set email alerts
|

Determinants Of Foreign Direct Investment In MENA Region: Panel Co-Integration Analysis

Abstract: <p>This paper aims<strong> </strong>to investigate the relationship between Determinants of Foreign Direct Investment (FDI) inflows and their determinants in MENA (Middle East and North Africa) region during the period 1970- 2010. Using panel data techniques, we take into account the both hypothesis economic dependencies and structural breaks. We find that the macro determinants like openness, growth rate, exchange rate, and economic instability have a long-run impact on FDI inflows in our pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 15 publications
2
18
0
Order By: Relevance
“…Additionally, for the control variables, our results of the first specification, our base model, show that TOP is associated positively with FDI inflows in the long-run. These results are in line with a large number of prior studies such as Chakrabarti (2001), Sekkat and Veganzones (2007), Moosa (2009), Rogmans (2013, Jabri et al (2013), Jabri and Brahim (2015), and Khayat (2017). The coefficient of TINF is negative and significant at 5% in the first model with a coefficient value of -0.015, implying that increasing in telecommunication infrastructure is associated with lower increase in FDI inflows in Algeria.…”
Section: Discussion Of Results and Conclusionsupporting
confidence: 91%
See 2 more Smart Citations
“…Additionally, for the control variables, our results of the first specification, our base model, show that TOP is associated positively with FDI inflows in the long-run. These results are in line with a large number of prior studies such as Chakrabarti (2001), Sekkat and Veganzones (2007), Moosa (2009), Rogmans (2013, Jabri et al (2013), Jabri and Brahim (2015), and Khayat (2017). The coefficient of TINF is negative and significant at 5% in the first model with a coefficient value of -0.015, implying that increasing in telecommunication infrastructure is associated with lower increase in FDI inflows in Algeria.…”
Section: Discussion Of Results and Conclusionsupporting
confidence: 91%
“…In this respect, we consider three control variables in our empirical model. Firstly, the total value of exports and imports of goods and services to GDP ratio is used as a proxy for trade openness (Jabri et al, 2013;Jabri and Brahim, 2015;Khayat, 2017). Secondly, the number of fixed and mobile phone subscriptions per thousand of the population is adopted to capture for telecommunications infrastructure indicator (TINF) (Rudra et al, 2017;Suh and Khan, 2003).…”
Section: Data Sources and Research Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…As a matter of fact, some researchers put forward that FDI is highly persistent, showing that the long-term effect of a variety of factors on FDI is much larger than that in the short term (Kamaly, 2003). Others, such as Jabri et al (2013), have also studied these effects in the MENA countries taking into account the economic dependencies between these countries and the effects of the economic crisis where the FDI evolution is affected by unclear periods. Taking into account all the reasons mentioned above, this research aims at investigating the effects of FDI factors in MENA region given the existence of economic dependencies between countries and effects of economic crisis where the evolution of the FDI is subject to unclear periods with an unsatisfactory MENA performance compared to other regions.…”
Section: Introductionmentioning
confidence: 99%
“…Hunady and Orviska (2014) also showed the factor affected the FDI in EU countries. Jabri and Brahim (2015) and Jabri et al (2013) also showed the determinants of FDI in the MENA region. This is the basis for my research in this paper.…”
Section: Factors Affecting the Attraction Of Foreign Investorsmentioning
confidence: 98%